2011
DOI: 10.1097/mpg.0b013e3181e2c6e2
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Evaluation of Dietary Treatment in Childhood Constipation: High Dietary Fiber and Wheat Bran Intake Are Associated With Constipation Amelioration

Abstract: High DF and bran intake are feasible in constipated children and contribute to amelioration of constipation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 30 publications
0
38
0
8
Order By: Relevance
“…Besides, studies have shown that constipation in children was associated with low dietary fibre intake (Jennings et al . 2009; Maffei & Vicentini 2011) and low consumption of fruit and vegetables (Lee et al . 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, studies have shown that constipation in children was associated with low dietary fibre intake (Jennings et al . 2009; Maffei & Vicentini 2011) and low consumption of fruit and vegetables (Lee et al . 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In adults and schoolchildren, it is known that increasing dietary fibre and fluid intake can be effective in amelioration of symptoms of constipation (Kokke et al . 2008; Maffei & Vicentini 2011). However, in pre‐school children, this approach has been controversial as the results of studies regarding dietary fibre and constipation in very young children are inconsistent (Roma et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Constipation involves painful physical symptoms that result in a lower quality of life [7,8]. Affected children have lower fiber intake than healthy children [5,9] and increasing bran and fiber intake can ameliorate symptoms [10]. The evidence for the association between fiber intake and constipation is robust and increasing dietary fiber is accepted as one of the first treatment recommendations [11].…”
Section: Introductionmentioning
confidence: 99%
“…Constipation is a highly prevalent functional gastrointestinal disorder, affecting the quality of life in constipated persons [7], and the use of dietary fiber in the prevention and treatment of constipation is a common practice in many countries of the world [16,28]. The present study has evaluated laxative effects of Salecan on normal as well as on loperamide- and clonidine-induced constipation mice.…”
Section: Discussionmentioning
confidence: 99%